Potential health threats: the impact of hukou-based labour market discrimination on the health of rural migrants - Yi, Qiuping; Li, Jingjing (Frontiers in Public Health, 2025)
The hukou system is a population management policy in China. However, existing research has paid little attention to the relationships between hukou-based labour market discrimination and the health of rural migrants. To fill this research gap, we empirically examine whether and how hukou-based labour market discrimination impacts the health of rural migrants by employing an ordered probit model with the data from the 2017 China Migrants Dynamic Survey (CMDS). Our findings indicate that hukou-based labour market discrimination still prevails in Chinese cities. This discrimination negatively impacts rural migrants’ self-rated health. Then, addressing endogeneity and robustness issues using extended regression models and instrumental variables, the conclusions remain valid. We also found that “Whether to seek treatment for illness” emerges as a pivotal mechanism by which hukou-based labour market discrimination affects the health of rural migrants. Additionally, “enrollment in the New Rural Cooperative Medical Insurance” effectively mitigates the adverse effects of such discrimination on the health of rural migrants. Our findings underscore crucial guidance for advancing the reform of China’s hukou system and improving the health of rural migrants through targeted government policies and social initiatives.